Overexpression of the poplar NF-YB7 transcription factor confers drought tolerance and improves water-use efficiency in Arabidopsis - Han, Xiao (Journal of experimental botany, 2013)
Water deficit is a serious environmental factor limiting the growth and productivity of plants worldwide. Improvement of drought tolerance and efficient water use are significant strategies to overcome this dilemma. In this study, a drought-responsive transcription factor, nuclear factor Y subunit B 7 (PdNF-YB7), induced by osmotic stress (PEG6000) and abscisic acid, was isolated from fast-growing poplar clone NE-19 [Populus nigra × (Populus deltoides × Populus nigra)]. Ectopic overexpression of PdNF-YB7 (oxPdB7) in Arabidopsis enhanced drought tolerance and whole-plant and instantaneous leaf water-use efficiency (WUE, the ratio of biomass produced to water consumed). Overexpressing lines had an increase in germination rate and root length and decrease in water loss and displayed higher photosynthetic rate, instantaneous leaf WUE, and leaf water potential to exhibit enhanced drought tolerance under water scarcity. Additionally, overexpression of PdNF-YB7 in Arabidopsis improved whole-plant WUE by increasing carbon assimilation and reducing transpiration with water abundance. These drought-tolerant, higher WUE transgenic Arabidopsis had earlier seedling establishment and higher biomass than controls under normal and drought conditions. In contrast, Arabidopsis mutant nf-yb3 was more sensitive to drought stress with lower WUE. However, complementation analysis indicated that complementary lines (nf-yb3/PdB7) had almost the same drought response and WUE as wild-type Col-0. Taken together, these results suggest that PdNF-YB7 positively confers drought tolerance and improves WUE in Arabidopsis; thus it could potentially be used in breeding drought-tolerant plants with increased production even under water deficiency